Determinants of Healthcare Choice in Kontagora Town (Lapai Journal of Economics, 2022)
This study examined the determinants of healthcare choice in Kontagora town. The objective was to investigate the factors that influence the choice of healthcare providing facility in the study area and to ascertain the extent at which the available healthcare facilities are accessible to the residents of the area. Data were retrieved through self interviewer-administered questionnaires involving 100 consenting participants selected through a random sampling technique. The study utilised the multiple regression equation. The study revealed that gender, marital status, education, and religion are significant factors that influence the choice of healthcare. The study also revealed that most respondents (about 45.7%) used the public health service. In comparison, only 38% preferred private healthcare services, indicating a growing trend towards private healthcare facilities as a choice of medical services among the people of Kontagora. The selection of healthcare service was attributed to cost and quality service, effective treatment, nearness of the facility, and waiting time. The study recommended that government and stakeholders play a significant role in increasing community-based health education, creating awareness, and improving access to information through public discussions and local media.